Forces for Good? - Duncanson, C. author. aut Link
XIII, 193 p.
Keywords: This book utilises the growing phenomenon of British soldier narratives from Iraq and Afghanistan to explore how British soldiers make sense of their role on these complex, multi-dimensional operations. It aims to intervene in the debates within critical feminist scholarship over whether soldiers can ever be agents of peace.